Mathematical modeling of the adhesion of reinforcement with high strength concrete - Marek Dohojda; Sergiy Filipchuk; Ruslan Makarenko (Acta Scientiarum Polonorum. Architectura)
The article presents the results of experimental researches of the bond between steel and high strength concrete. According to the results of the experiment planned, the regression equation can be used in aim to analyze an impact of specific factors on the limit stresses on the surface of concrete and a steel bar, as well as to normalize the limit stresses of the bond. The adequacy of the mathematical models of bonds to the experimental data has been proved by the statistical methods.